ANALISIS KEPUASAN PELANGGAN PT PLN (Persero) TERHADAP PROSES PEMASANGAN LISTRIK PRABAYAR (Studi Kasus PT PLN WS2JB Rayon Sukarami) - MARKONI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
The research is aimed to analyze customers satisfaction of PT PLN (Ltd) inline with the installation process of prepaid electricity. It is case study whereas the research are mainly focus on Customers of PLN in Sukarami ditrict. the. There are two main problems in this research. Firstly, What factors affect the customer satisfaction inline with the installation of prepaid electricity. Secondly, whiich dimension of service quality dominantly affect the PLN’ customers. The research mainly used primary data by delivering questionaires to selected respondents. The questionaire was delivered to 99 selected respondents. The research used purposive sampling. The Interpretation Score is also used to analyze the research. The results of the research shows that Interpretation score of each dimension are high. It shows that customers of PT PLN (Ltd) highly satisfy with the installation process of prefepaid electricity. The research also shows that assurance dimension has great affect or dominant factors (83.93 %) that influence the customer satisfaction.